Histological characteristics of the sexual segment of the kidney of three species of Amphisbaenia (Reptilia: Squamata) - Valverde, Maria Celeste C.; Scherer, Paulo O.; Pinheiro, Nadja L. (SITIENTIBUS série Ciências Biológicas, 2005)
The shape and structure of the sexual segment of the kidney of Amphisbaena vermicularis Wagler, 1824, Amphisbaena alba Linnaeus, 1758 and Leposternon polystegum Duméril, 1851, were histologically analyzed on a sample of 30 sexually active males, all coming from the municipal district of Feira de Santana, Bahia, Brasil. Fragments of the kidneys and of the gonads were fixed in Bouin solution by a period of 24 hours and conserved in alcohol at 70%. After having fixed and dehydrated, the material was diaphanicized, included in paraffin, and the sections obtained were stained with hematoxilin-eosin (HE). Changes in the height of the epithelium, in the diameter of the tubes and in the amount of the granules of secretion of the cells in the sexual segment of the kidney are notedly different and they happen in a cyclic forn during the spermatogenesis process. The histological characteristics described for the sexual segment of the hypertrophied kidney, or in atrophy during the testicular resting, were found without variations in the adult males of the three analyzed species, and they are similar to structural patterns known for other males of Squamata.